TEM and High Resolution TEM Investigation of Phase Formation in High Entropy Alloy AlCrFe2Ni2 - Eshed, Eyal; Abd El Majid, Suzan; Bamberger, Menachem; Osovski, Shmuel (Frontiers in Materials, 2020)
The AlCrFe2Ni2 high entropy alloy exhibits an interesting microstructure, which changes considerably when various thermal treatments are applied. These changes are manifested mostly through the precipitation and dissolution of several BCC and FCC phases. To gain better understanding as to the phase evolution in AlCrFe2Ni2 with respect to the thermal history, the microstructures of four thermal states were investigated using Transmission Electron Microscope (TEM) and high resolution TEM. The thermal states included as-cast, homogenized at 1185°C for 75 minutes, homogenized and aged at 750°C for 4 hours, and homogenized and aged at 930°C for 3 hours. Common phases to all of the examined thermal states are Fe-rich FCC phase, ordered Ni-Al -rich BCC phase (B2), and disordered Cr-Fe -rich BCC phase. Following homogenization at 1185°C dissolution of the submicron-sized BCC phase particles in the ordered B2 phase was observed. Ageing at 750°C resulted in the precipitation of nano-sized B2 platelets and needle-like particles inside the FCC phase domain, while the re-precipitation of nano-sized Cr-Fe globules occurred in the B2 phase. Ageing at 930°C resulted mainly in the formation of submicron sized B2 platelets in the FCC phase domain.